Characterization of Chitosanase from Indralaya Swamp Bacteria, South Sumatera, Indonesia - Baehaki, Ace; Herpandi (Asian Journal of Chemistry, 2013)
The extracellular chitosanase-production capacity of 14 bacterial isolates taken from Indralaya Swamp South Sumatera, was evaluated in liquid cultures. The GB2 isolate was selected due to its high chitosanase activity. The optimum pH and temperature of chitosanase produced by GB2 were 8 and 30 ºC, respectively. Ca2+ and Fe2+ increased GB2 chitosanase whereas Na+ and K+ inhibited the enzyme. Study on the effect of metals ion indicated that chitosanase GB2 was metaloenzyme. Moleculer weights were determined by using SDS-PAGE and zymogram technique. Moleculer weight of chitosanase isolate GB2 was 36-110 kD.